Charting death penalty abolition through abolitionist de facto states - Clesi, AB (2024)
This dissertation explores the phenomenon of abolitionist de facto (in practice) (ADF) states in the United States (US). These states, located primarily in the Midwestern and Western US, retain the death penalty de jure (in law) but have not carried out any executions in at least 10 years. Focusing on Kansas and Wyoming, this research challenges the assumption that ADF status inevitably leads to abolition de jure. Instead, it argues that ADF jurisdictions may remain vulnerable to the resumption of executions due to various political and social factors.